Pengaruh Persepsi Kegunaan, Kemudahan dan Risiko Terhadap Minat Membayar Zakat, Infaq dan Shodaqoh Menggunakan Fitur Berbagi-Ziswaf BSI - Habibah, Umi; Nurafini, Fira (Jurnal Ekonomika dan Bisnis Islam, 2024)
ZIS funds are the most important instrument in improving the country's welfare in the context of sharia economics. The potential for obtaining ZIS funds and receipt of ZIS funds in Indonesia is experiencing a gap. BAZNAS has designated UPZ (Zakat Management Unit), one of which is BSI, as a service unit tasked with serving muzakki by providing Zakat, Infaq and Shodaqoh (ZIS) payment features, namely the Sharing-Ziswaf feature on BSI mobile banking. This research aims to analyze the influence of perceived usefulness, perceived easy and perceived risk on customers' interest in paying Zakat, Infaq and Shodaqoh (ZIS) using the ziswaf-sharing feature on Bank Syariah Indonesia's mobile banking. Data were analyzed using the SEM-PLS technique. The total number of respondents who filled out the questionnaire were 106 people who were BSI customers. The data source used in this research comes from primary data. Sampling used a purposive sampling technique. The results of the study showed that perceived usefulness and perceived easy had a positive effect on customers' interest in paying ZIS using the ZIS-sharing feature on BSI mobile banking while perceived risk had a negative effect on customers' interest in paying ZIS using the ZIS-sharing feature on mobile BSI banking.